Mating system transitions in Solanum habrochaites impact interactions between populations and species. Issue 1 (12th August 2016) - Broz, Amanda K.; Randle, April M.; Sianta, Shelley A.; Tovar‐Méndez, Alejandro; McClure, Bruce; Bedinger, Patricia A.
Summary: In plants, transitions in mating system from outcrossing to self‐fertilization are common; however, the impact of these transitions on interspecific and interpopulation reproductive barriers is not fully understood. We examined the consequences of mating system transition for reproductive barriers in 19 populations of the wild tomato species Solanum habrochaites . We identified S. habrochaites populations with self‐incompatible (SI), self‐compatible (SC) and mixed population (MP) mating systems, and characterized pollen–pistil interactions among S. habrochaites populations and between S. habrochaites and other tomato species. We examined the relationship between mating system, floral morphology, interspecific and interpopulation compatibility and pistil SI factors. We documented five distinct phenotypic groups by combining reproductive behavior with molecular data. Transitions from SI to MP were not associated with weakened interspecific reproductive barriers or loss of known pistil SI factors. However, transitions to SC at the northern range margin were accompanied by loss of S‐RNase, smaller flowers, and weakened (or absent) interspecific pollen−pistil barriers. Finally, we identified a subset of SC populations that exhibited a partial interpopulation reproductive barrier with central SI populations. Our results support the hypothesis that shifts in mating system, followed by additional loss‐of‐function mutations, impact reproductive barriers within and between species.